Water ingress into a casein film quantified using time-resolved neutron imaging. Issue 9 (10th February 2016) - Metwalli, E.; Hermes, H. E.; Calzada, E.; Kulozik, U.; Egelhaaf, S. U.; Müller-Buschbaum, P.
Abstract : Migration of water into a casein film was probed with neutron radiography and the water saturation quantitatively analyzed. Abstract : The migration of water into a casein film was probed with neutron radiography. From the neutron transmission images, the evolution of the water saturation profiles was extracted. The results indicate that the water influx is dominated by imbibition but also contains a diffusional component. The time dependence of the water ingress was quantified using a diffusion-like equation previously also applied to imbibition. A water transport coefficient D = 0.9 × 10 −9 m 2 s −1 was found. This value and direct observation of the images indicate that the time taken for a typical adhesive casein-based layer to become saturated with water is of the order of hours.